Regulation in health care: the role of nurses - Peiter, Caroline Cechinel; Lanzoni, Gabriela Marcelino de Melo; Oliveira, Walter Ferreira de (Rev Rene, 2016)
Objective: to understand the activities developed by nurses in the context of regulation in health care. Methods: this is a qualitative study with techniques of focal group (with eight subjects), participant observation and documentary analysis. Results: the subcategories Nurse’s role in the Regulation sector and Interface of the activities of the nurse working in the Regulation sector with the other professionals revealed the presence of nurses in leadership positions and their articulation with management and managers. Competencies such as communication, leadership, decision-making, planning, personnel management and teamwork were highlighted, and permanent education was perceived as a strategy for process improvement and team qualification. Conclusion: the participating nurses understand the activities they develop in the context of regulation in health care aimed at communication, leadership, decision-making, planning, personnel management and teamwork, which are instruments for autonomous action in the managerial context.